Two different timing of intra uterine insemination in patients of unexplained infertility: a randomized clinical trial - Elsersy, Mervat A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unexplained infertility is diagnosed when the basic infertility workup is found to be normal. The objective was to compare between the results of IUI performance at 24 hours or 36 hours after hCG injection in couples with unexplained infertility. Methods: A prospective comparative study was conducted on 250 patients diagnosed with unexplained infertility who were randomly allocated in two equal groups. Each patient received ovulation induction. Follicular growth scanning was performed, patients received 10.000 hCG injection when there was mature follicle equaled to or more than 18mm. Then they randomly allocated to either group 1 who underwent IUI 24 hours after hCG injection or group 2 who underwent IUI 36 hours after hCG injection. Results: The positive qualitative serum β -hCG test was higher in group 1 who received IUI 24 hours after hGC injection, 24%, while in group 2 who received IUI 36 hours after hGC injection, it was 16.8% but no statistical differences between the two studied groups could be observed. The most important finding in this study is that the clinical pregnancy rate in group 1 was significantly higher than in group 2. Conclusions: Earlier IUI procedures increased the clinical pregnancy rate in patients with unexplained infertility during ovulation induction with gonadotropins. Correct timing of insemination is essential.